Protein S Deficiency and The Mechanism of Protein S in Hemostasis and Atherosclerosis - Nur Feby Febiana Agistany; Ananda Karunia Ramadhan; Dira Kurnia Rizki; Raditya Bayu Farizil Akhyar; Ilsa Hunaifi (Jurnal Biologi Tropis, 2023)
Protein S (PS) is Vitamin K dependant protein which plays a role in regulating the blood clotting process in the body. Protein S deficiency is explained as a condition characterized by reduced levels of protein S in the serum so that it makes the blood clot too easily. The purpose of this literature review is to give an update of protein S defficiency and the mechanism of protein s in hemostasis and atherosclerosis based on publish literature reference from various database. Protein S plays important role in hemostasis by regulating blood cloth process in the initiation phase of the extrinsic pathway as a TFPI cofactor or in the propagation phase, namely as an APC cofactor and independent activity of TFPIα and APC. Protein S deficiency is known to be associated with the occurrence of atherosclerosis via the Tyro3-Axl-Mer (TAM) receptor. The main clinical manifestations of the majority of patients with heterozygous mutations in the protein S (PROS1) gene are deep vein thrombosis (DVT) and pulmonary embolism that precipitate by VTE. Administration of anticoagulant drugs such as heparin in the form of low-molecular-weight heparin (LMWH) or unfractionated heparin, vitamin K antagonists (VKA), namely warfarin, or direct oral anticoagulants (DOACs) can be selected as a management of protein S deficiency with VTE. Protein S has a central role in the coagulation prosses and its deficiency associated with atherosclerotic conditions.